Frontispiece: Donor‐Flexible Nitrogen Ligands for Efficient Iridium‐Catalyzed Water Oxidation Catalysis. Issue 20 (10th May 2016) - Navarro, Miquel; Li, Mo; Müller‐Bunz, Helge; Bernhard, Stefan; Albrecht, Martin
Abstract : Ligand Design A ligand that adapts to its environment like a chameleon has been utilized for coordination to iridium. By swapping between a neutral π‐acidic resonance form (the green chameleon) and a π‐basic zwitterionic form (red chameleon), different metal oxidation states can be stabilized. These properties have been applied for developing a very efficient water oxidation catalyst (artwork by M. Navarro). For more details, see the Communication by S. Bernhard, M. Albrecht et al. onpage 6740 ff.